Neonatal hypoglycemia, early-onset diabetes and hypopituitarism due to the mutation in EIF2S3 gene causing MEHMO syndrome - Staník, Juraj; Škopková, Martina; Staníková, Daniela; Brennerová, K; Barák, Ľubomír; Tichá, Ľubica; Hornová, Jarmila; Klimeš, Iwar; Gašperíková, Daniela (Physiological research, 2018)
Recently, the genetic cause of several syndromic forms of glycemia dysregulation has been described. One of them, MEHMO syndrome, is a rare X-linked syndrome recently linked to the EIF2S3 gene mutations. MEHMO is characterized by Mental retardation, Epilepsy, Hypogonadism/hypogenitalism, Microcephaly, and Obesity. Moreover, patients with MEHMO had also diabetes and endocrine phenotype, but detailed information is missing. We aimed to provide more details on the endocrine phenotype in two previously reported male probands with MEHMO carrying a frame-shift mutation (I465fs) in the EIF2S3 gene. Both probands had a neonatal hypoglycemia, early onset insulin-dependent diabetes, and hypopituitarism due to dysregulation and gradual decline of peptide hormone secretion. Based on the clinical course in our two probands and also in previously published patients, neonatal hypoglycemia followed by early-onset diabetes and hypopituitarism may be a consistent part of the MEHMO phenotype.
Keywords: Microcephaly; hypogonadismus; Epilepsy; Phenotype; hypoglykemie; novorozenec; transkripční faktory; Hypopituitarism; mikrocefalie; endokrinní žlázy; Obesity; lidé; posunová mutace; Infant, Newborn; pohlavní orgány; Transcription Factors; Frameshift Mutation; Endocrine Glands; Diabetes Mellitus, Type 1; eukaryotický iniciační faktor 2; epilepsie; Hypogonadism; X-Linked Intellectual Disability; obezita; Male; hypopituitarismus; mentální retardace vázaná na chromozom X; fenotyp; mužské pohlaví; Eukaryotic Initiation Factor-2; diabetes mellitus 1. typu; Genitalia; Hypoglycemia; Humans